Lexicografia i cultura: antropologia i sistema social (noms, renoms i noms de casa al Pirineu aragonès) - Pujadas, Joan J.; Comas, Dolors (Caplletra. Revista Internacional de Filologia, 2015)
In this article we analize the system of names, individual nicknames and household nicknames. The empirical information was obtained from ethnographic fieldwork in two villages of the central Pyrenees. Anthroponims serve to denominate individuals; they also classify them according to their place in the family and in the community. Finally, anthroponims evoke meanings and symbols culturally constructed.